Construction of a front_end compiler for vector languages - Βρουστούρης, Παναγιώτης (Πανεπιστήμιο Πελοποννήσου, 2012)
Vector languages such as MATLAB have become popular for many years in prototyping algorithms in various domains. Many of these applications whose subtasks have diverse execution requirements, often employ distributed, heterogeneous, reconfigurable systems. These systems consist of an interconnected set of heterogeneous processing resources that provide a variety of architectural capabilities. The MATCH (MATlab Compiler for Heterogeneous computing systems) compiler project, developed at Northwestern University, is to make it easier for the users to develop efficient code for distributed, heterogeneous, reconfigurable computing systems. In the current project, I use the context–free grammar of the MATCH compiler to the design and implement a front_end compiler using a full object-oriented schema. I present the execution results on some test MATLAB code with the use of this front_ end compiler.
Μ.Δ.Ε. 11
Keywords: Μεταγλωττιστές (Προγράμματα ηλεκτρονικών υπολογιστών); Ηλεκτρονικοί υπολογιστές -- Γλώσσες προγραμματισμού; Context-free grammar; Scanner; Parser; M-Files; Flex; Bison; Non-terminals; Statements; Expressions; Assignments; Parse errors; Intermediate representation abstract; Syntax tree; DOT files